2007
DOI: 10.1007/s11033-007-9121-3
|View full text |Cite
|
Sign up to set email alerts
|

The JMJD2 members of histone demethylase revisited

Abstract: The study of histone lysine demethylases has become very hot recently. Many histone demethylases have been reported by different research groups with various techniques. However, how many histone lysine-methylation states can be removed by one specific demethylase and how many demethylases can remove one specific histone lysine-methylation state? It remains a daunting challenge to answer these questions to date. An in-depth discussion on recent results, three important points were provided: (1) Some demethylas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Histone demethylases, such as members of the Jumonji family, revert histone methylation (24). In neural crest development, JmjD2A (also known as KDM4A) regulates neural crest specification (18).…”
Section: Discussionmentioning
confidence: 99%
“…Histone demethylases, such as members of the Jumonji family, revert histone methylation (24). In neural crest development, JmjD2A (also known as KDM4A) regulates neural crest specification (18).…”
Section: Discussionmentioning
confidence: 99%
“…These demethylases remove tri-methyl groups from lysine residues. The function of these enzymes has been analyzed mainly during the early stages of development, with the JmjD2 sub-family involved in the demethylation of various lysine residues in undifferentiated and differentiated embryonic stem cells [58]. Concerning regulation of posterior development in animals, JMJD3 counterbalances the activity of PcG group proteins with respect to the state of lysine 27 of histone H3 [59].…”
Section: Perspectivesmentioning
confidence: 99%
“…Among these modifications, important downstream effects on chromatin functionalities are proposed to occur upon methylation of specific lysine residues in histone proteins H3 and H4 [2][3][4][5]. Previously, methylation reaction on histone proteins have been thought to be irreversible and removal of the methylation has only been obtained by switching of the elder histone protein with a new molecule [6][7][8]. Recent studies, on the contrary, showed that methylation removal from the lysine residues are not irreversible [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that, enzymes member of JMJD2 family are closely related with human cancers, thus promising as cancer targets [6,[12][13][14]. Among the members of JMJD2 family, the JMJD2A enzyme is indicated to be involved in human prostate cancer via binding to the Androgen receptor (AR) and Retinoblastoma protein (Rb) thus interfering the functionalities of these proteins [12,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation